How Do Infants Disaggregate Referential and Affective Pitch? - Kager, René (Frontiers in Psychology, 2018)
Infants are faced with a challenge of disaggregating functions of pitch in the ambient language into affective, pragmatic or referential (the latter in tone languages only). This mini review discusses several factors that might facilitate the disaggregation of referential and affective pitch in infancy: acoustic characteristics of infant-directed speech, recognition of vocal affect, facial cues accompanying affective prosody, and lateralization of affective and referential prosody in the brain. It proposes two hypotheses concerning the role of audiovisual cues and brain lateralization